2022
DOI: 10.3389/fenvc.2022.853764
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pollutant Concentrations in Urban Stormwater Across Eastern Australia, After 20 Years

Abstract: Concerns about pollutants in urban stormwater were initially raised in the early 1970s. Australian investigations decades later, also found urban stormwater runoff contained elevated levels of sediment and nutrients, as well as heavy metals, that brought stormwater management to the forefront for regulators. Planning policies were implemented to integrate stormwater management into development in the form of water sensitive urban design (WSUD), also known internationally as low-impact design (LID) and Sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…However, the average TN concentrations in the residential catchment (2.225 mg/L) are rather similar to the industrial catchment (2.525 mg/L). Drapper et al (2022)'s review reported a mean TN concentration of 1.06 mg/L in untreated stormwater runoffs in the Melbourne region, which is lower than the results of this study, however, the study did not specify the catchment characteristics. Meanwhile, Shi et al (2019) reported higher levels of TN in both industrialized and residential areas, concluding that land use does not influence pollutant concentrations, which supports the results of this study.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…However, the average TN concentrations in the residential catchment (2.225 mg/L) are rather similar to the industrial catchment (2.525 mg/L). Drapper et al (2022)'s review reported a mean TN concentration of 1.06 mg/L in untreated stormwater runoffs in the Melbourne region, which is lower than the results of this study, however, the study did not specify the catchment characteristics. Meanwhile, Shi et al (2019) reported higher levels of TN in both industrialized and residential areas, concluding that land use does not influence pollutant concentrations, which supports the results of this study.…”
Section: Resultscontrasting
confidence: 89%
“…The results matched with Li et al (2015)' study where the residential area was found with higher event mean concentrations of TP and TSS. In particular, TP ranged from 0.05 to 0.26 mg/L which is quite similar to other studies conducted in the same region (Drapper, Olive, McAlister, Coleman, & Lampard, 2022;Shi et al, 2019). However, the average TN concentrations in the residential catchment (2.225 mg/L) are rather similar to the industrial catchment (2.525 mg/L).…”
Section: Resultssupporting
confidence: 85%